Low-cost and high-performance visual guidance and navigation system for space debris removal. (17th November 2021) - Kimura, Shinichi; Atarashi, Eijiro; Kashiwayanagi, Taro; Fujimoto, Kohei; Proffitt, Ryan
Abstract : A highly intelligent visual guidance navigation system that can autonomously identify target space debris and realize a controlled rendezvous maneuver is required to mitigate space debris. In this study, such a system is developed by integrating autonomous control software technologies and commercial off-the-shelf (COTS) devices. The orbital performance of the COTS-based intelligent camera system of the end-of-life services is demonstrated during an Astroscale-demonstration mission, a technology demonstration mission for satellite end-of-life services. For this mission, Astroscale collaborated with the Tokyo University of Science to develop a visual guidance and navigation system for space debris Removal. In this regard, this paper reports the design and performance of a COTS-based intelligent camera system for space debris Removal. GRAPHICAL ABSTRACT: UF0001